Solitary Wave Solutions for the Generalized Zakharov-Kuznetsov- Benjamin-Bona-Mahony Nonlinear Evolution Equation (Global Journal of Science Frontier Research, 2016)
In this paper, we employ the exp (-φ(ξ))-expansion method to find the exact traveling wave solutions involving parameters of nonlinear evolution equations. When these parameters are taken to be special values, the solitary wave solutions are derived from the exact traveling wave solutions. It is shown that the proposed method provides a more powerful mathematical tool for constructing exact traveling wave solutions for many other nonlinear evolution equations.
Keywords: the exp (- 3C6; (3BE; )) -expansion method; the generalized zakharov-kuznetsov- benjamin-bona-mahony nonlinear evolution equation; traveling wave solutions